THE EFFECT OF FRACTURE HANDLING SIMULATION THROUGH TV TUBE STREAMING ON STUDENT PREPAREDNESS IN HANDLING FRACTURES AT HIGH SCHOOL AL ISLAM 1 SURAKARTA - Saputro, Sutiyo Dani; Afni, Anissa Cindy Nurul; Suroso, Heri; Saelan, Saelan; Kusumaningrum, Bintari Ratih (SYNTIFIC, 2023)
Background. Injuries from accidents in the school environment generally occur in the musculoskeletal system and must be treated quickly and appropriately. Injury will cause bleeding, bone deformity or disability and even death. Splint dressing relief can be performed by any trained layperson. One of the lay people trained at school is a student who has received basic emergency education. Improving fracture treatment in students can be done by online simulation using Streaming Tv Tube. The purpose of this study was to determine the effect of fracture handling simulation through TV Tube streaming on student preparedness in handling fractures Research Method. This type of research is a quantitative study using a Quasi-Experimental research design with a pre-post-test without control by providing a TV Tube streaming simulation intervention in one group without a comparison. The research sample was 43 students of SMA Al Islam 1 Surakarta. Data analysis was performed using the Wilcoxon test Findings. The results of the Wilcoxon test showed a p-value of 0.000 so there was an effect of simulation on handling fractures through streaming TV tube on students' preparedness in handling fractures. Conclusion. There is a difference in students' preparedness in providing treatment for fractures before and after being given a fracture handling simulation intervention via TV Tube streaming. Before being given the intervention, it was shown that almost all respondents had almost ready preparedness, whereas after being given the intervention, most of the respondents had ready preparedness.